The first zoeal stage morphology of Achelous spinimanus (Latreille), A. gibbesii (Stimpson), and Portunus sayi (Gibbes) (Decapoda, Brachyura) provides support for molecular phylogeny - Mantelatto, Fernando L.; Pantaleão, João A. F.; Cuesta, José A.; Fransozo, Adilson; Felder, Darryl L. (Zootaxa, 2018)
Taxonomic rearrangements were recently proposed for some members of Portunus Weber and Cronius Stimpson, including the re-elevation of the status of the subgenus Achelous De Haan to accommodate 21 American species. In the present study the first zoea of Achelous spinimanus, type species of the genus, A. gibbesii and Portunus sayi were obtained from laboratory-hatched specimens. The morphology of the first zoeal stage of A. spinimanus is described and illustrated for the first time. Those of A. gibbesii and P. sayi are redescribed in detail using standard terminology and compared with previous unpublished descriptions. Differences are listed and remarks from a comparative analysis of available descriptions of other portunid genera and species with a known first zoeal stage are furnished. The larval morphology pattern observed in the studied species corroborates a previous hypothesis on the phylogeny of the group.